Randomised controlled trial of intravenous antibiotic treatment for cellulitis at home compared with hospital. Issue 7483 (16th December 2004) - Corwin, Paul; Toop, Les; McGeoch, Graham; Than, Martin; Wynn-Thomas, Simon; Wells, J Elisabeth; Dawson, Robin; Abernethy, Paul; Pithie, Alan; Chambers, Stephen; Fletcher, Lynn; Richards, Dee
Abstract: Objectives To compare the efficacy, safety, and acceptability of treatment with intravenous antibiotics for cellulitis at home and in hospital. Design Prospective randomised controlled trial. Setting Christchurch, New Zealand. Participants 200 patients presenting or referred to the only emergency department in Christchurch who were thought to require intravenous antibiotic treatment for cellulitis and who did not have any contraindications to home care were randomly assigned to receive treatment either at home or in hospital. Main outcome measures Days to no advancement of cellulitis was the primary outcome measure. Days on intravenous and oral antibiotics, days in hospital or in the home care programme, complications, degree of functioning and pain, and satisfaction with site of care were also recorded. Results The two treatment groups did not differ significantly for the primary outcome of days to no advancement of cellulitis, with a mean of 1.50 days (SD 0.11) for the group receiving treatment at home and 1.49 days (SD 0.10) for the group receiving treatment in hospital (mean difference 0.01 days, 95% confidence interval -0.3 to 0.28). None of the other outcome measures differed significantly except for patients' satisfaction, which was greater in patients treated at home. Conclusions Treatment of cellulitis requiring intravenous antibiotics can be safely delivered at home. Patients prefer home treatment, but in this study only about one third of patients presenting at hospital for intravenous treatment of cellulitis were considered suitable for home treatment.